EVALUASI KEBIJAKAN PENANGGULANGAN KEMISKINAN (Studi Pelaksanaan Perda Nomor 2 Tahun 2007 Tentang Penanggulangan Kemiskinan di Kabupaten Kutai Kartanegara) - Efri Novianto (Pusjar SKPP Lembaga Administrasi Negara, 2012)
One of our national goals is to realize people well-being. When local autonomy was applied, it is the mutual responsibility between local government and central government for making people prosperous. District government of Kutai Kartanegara, in its effort to eradicate poverty, has issued policy through Local Regulation Number 2 Year 2007. Based on the data analysis, it can be concluded that the implementation of Local Regulation Number 2 Year 2007 did not run well. This can be seen from the fact that some of the policies and programs did not work well. This was caused by the quality of Local Regulation Number 2 Year 2007 which was not good enough because it only regulated technical and operational matters. TKPKD as a coordinating forum for poverty eradication did not play its role and function optimally. There was still sectoral ego from each SKPD in implementing the poverty eradication program. Data and information used as the basis for poverty eradication were out of date. Their reliability were unguaranteed, and the budget allocated for poverty eradication was very low and not comparable with the number of poor people in the District. The outcomes of this Local Regulation showed that there was a decrease in the number of poor people either in macro level (survey) or micro level (census) and this regulation was not effective in eradicating poverty in Kutai Kartanegara. Keywords : Local Autonomy, Local Regulation, Poverty Eradication Salah satu tujuan negara kita adalah mewujudkan kesejahteraan masyarakat. Ketika otonomi daerah diberlakukan, tanggung jawab untuk mensejahterakan masyarakat menjadi tanggung jawab bersama antara pemerintah pusat dengan pemerintah daerah. Pemerintah Daerah Kabupaten Kutai Kartanegara dalam rangka menanggulangi kemiskinan telah mengeluarkan Perda Nomor 2 Tahun 2007. Berdasarkan analisis data, maka bisa disimpulkan bahwa Pelaksanaan Perda Nomor 2 Tahun 2007 tidak berjalan dengan baik, hal ini bisa dilihat dengan tidak jalannya beberapa kebijakan dan program. Hal ini disebabkan oleh kualitas Perda Nomor 2 Tahun 2007 kurang baik karena terlalu mengatur hal-hal yang besifat teknis operasional, TKPKD selaku forum koordinasi penanggulangan kemiskinan peran dan fungsinya tidak optimal, masih adanya ego sektoral masing-masing SKPD dalam melaksanakan program penanggulangan kemiskinan, data dan Informasi sebagai landasan penanggulangan kemiskinan adalah data lama sehingga tidak terjamin validitasnya dan anggaran penanggulangan kemiskinan yang rendah dan tidak sebanding dengan jumlah penduduk miskin di Kabupaten Kutai Kartanegara. Hasil pelaksanaan perda ini adalah telah terjadi penurunan jumlah penduduk miskin di Kabupaten Kutai Kartanegara baik secara makro (survei), maupun mikro (sensus). Sementara dari segi efektivitas, Perda ini tidak efektif dalam menanggulangi kemiskinan di Kabupaten Kutai Kartanegara. Kata kunci: Otonomi Daerah, Perda, Efektivitas Penanggulangan Kemiskinan